Welding principles and applications - Jeffus, Larry F. (Delmar Cengage Learning, 2012)
Includes welding processes, technologies, techniques and practices. This title contains hundreds of photographs and illustrations, as well as environmental and conservation tips. It also contains expanded material on Plasma Cutting, FCAW, GMAW, and new Chapters on Shop Math, Reading Technical Drawings, and Fabricating.